Association between 5-Hydroxytryptamine Receptor 2A Gene (rs6313 and rs4941573) Polymorphism and Sleep Bruxism: A Meta-analysis - Motahari, Paria; Katebi, Katayoun; Pournaghi-Azar, Fatemeh; Jabbarzadeh, Masoumeh (Sleep Science, 2023)
Genetic factors may influence sleep bruxism's pathogenesis. Even though the association between the, 5-hydroxytryptamine 2A (5-HTR2A) serotonin receptor gene polymorphism and sleep bruxism has been investigated, inconsistent findings have been discovered. As a result, meta-analysis was performed to gather complete results on this topic. PubMed, Web of Science, Embase, and Scopus databases were searched for all papers containing English abstracts until April 2022. Medical Subject Heading (MESH) terms plus unrestricted keywords were used in the searches. The Cochrane test and the I2 statistic were used to determine the heterogeneity percentage in numerous researches. Comprehensive Meta-analysis v.2.0 software was used to conduct the analyses. Five properly fitting papers were chosen for meta-analysis from the 39 articles acquired during the initial search. The meta-analysis revealed that the 5-HTR2A polymorphism has no link with sleep bruxism susceptibility across the models studied (P-Value > 0.05). The combined odds ratio analysis revealed no statistically significant association between the 5-HTR2A gene polymorphism with sleep bruxism. Nonetheless, these findings require confirmation through researches with large sample sizes. Identifying genetic markers for sleep bruxism may help clarify and expand our current knowledge of bruxism physiopathology.
Keywords: Polymorphism; Genetic; Sleep Bruxism; Receptors; Serotonin; Meta-Analysis